2018
DOI: 10.1002/jcb.27313
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA C21orf121/bone morphogenetic protein 2/microRNA‐140‐5p gene network promotes directed differentiation of stem cells from human exfoliated deciduous teeth to neuronal cells

Abstract: Previous studies have revealed that long noncoding RNA (lncRNA) and microRNA play a crucial role in autism, which is a childhood neurodevelopmental disorder with complicated genetic origins. Hence, the study concerns whether lncRNA C21orf121/bone morphogenetic proteins 2 (BMP2)/miR‐140‐5p gene network affects directed differentiation of stem cells from human exfoliated deciduous teeth (SHED) to neuronal cells in rats with autism. Autism models were successfully established. The neuron cells that differentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Several canonical and non-canonical Bmp2 signaling pathways have been reported involved in odontogenesis ( Cho et al, 2010 ; Qin et al, 2012a ; Qin et al, 2012b ; Washio et al, 2012 ; Qin et al, 2014 ). Recently accumulated evidence has demonstrated that lncRNAs play biological roles in dental cell proliferation, cell proliferation, and tooth development through the regulation of growth and transcriptional factors ( Zheng and Jia, 2016 ; Liu et al, 2018 ; Gil and Ulitsky, 2020 ; Wang et al, 2020 ; Li et al, 2021 ; Mirzadeh Azad et al, 2021 ). The cross talk between the Bmp2 signaling pathway and lncRNAs in dental cell proliferation, cell differentiation, and odontogenesis remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several canonical and non-canonical Bmp2 signaling pathways have been reported involved in odontogenesis ( Cho et al, 2010 ; Qin et al, 2012a ; Qin et al, 2012b ; Washio et al, 2012 ; Qin et al, 2014 ). Recently accumulated evidence has demonstrated that lncRNAs play biological roles in dental cell proliferation, cell proliferation, and tooth development through the regulation of growth and transcriptional factors ( Zheng and Jia, 2016 ; Liu et al, 2018 ; Gil and Ulitsky, 2020 ; Wang et al, 2020 ; Li et al, 2021 ; Mirzadeh Azad et al, 2021 ). The cross talk between the Bmp2 signaling pathway and lncRNAs in dental cell proliferation, cell differentiation, and odontogenesis remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that Bmp2 regulates dental differentiation and dentinogenesis via these genes. It has been documented that the interplay of Bmp2 signal–associated mRNAs and lncRNAs regulates tooth development and formation ( Liu et al, 2018 ; Zhong et al, 2020 ). This study showed that several novel lncRNAs such as lncRNA87211.1, lncRNA87189.1, and lncRNA86888.1 co-expressed with those mRNAs ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA MSNP1AS expression was elevated in the postmortem cerebral cortex of individuals with ASD, which was mimicked by overexpression of MSNP1AS in human NPCs reduced neurite number and neurite length by disrupting moesin protein level, when knockdown of MSNP1AS blocked 318 genes expression, most of which participating in chromatin organization and immune response [72,79]. Moreover, lncRNA C21orf121 overexpression promoted conversion of stem cells from human exfoliated deciduous teeth into neuronal cells via acting as ceRNA of miR-140-5p to regulate BMP2 expression, which may provide a new therapeutic tool for ASD [80] (Table 3). Furthermore, lncRNAs are involved in angiogenesis that NPCs in SVZ and SGZ migration to ischemic zone for restoration of blood supply after ischemic stroke [81].…”
Section: The Effect Of Lncrna On Neurodevelopmental Disorder Via Targmentioning
confidence: 99%
“…Yang et al[ 78 ] found that Noggin overexpression combined with the Rho kinase inhibitor Y-27632 exhibited a synergistic effect in promoting differentiation of SHED into neuron-like cells[ 78 ]. The lncRNA C21orf121 promotes SHED differentiation into neuronal cells by upregulating the expression of BMP2, acting as a competing endogenous RNA to compete with BMP2 binding to miR-140-5p[ 79 ]. SHED in polyglycolic acid tubes combined with autografting can regenerate the mandibular branch of the rat facial nerve[ 80 ].…”
Section: Diverse Differentiation Of Dmscsmentioning
confidence: 99%